The inverse of a function f(x) is obtained by asuuming f(x)=y, and then solving for x, and then replacing x by y .
Given data:
it is given that the amount a plumber charges is modeled by f(x) = 75 +49x
(a)
Now to find the inverse of the function let f(x)=y so that
![\begin{gathered} 75+49x=y \\ 49x=y-75 \\ x=(y-75)/(49) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o6of01dw2zjkw9buebrb5f9qmgjtreoc8z.png)
Now on replacing y by x we get:
![f^(-1)(x)=(x-75)/(49)](https://img.qammunity.org/2023/formulas/mathematics/college/sncm6hjpvx575r1vne2uxdgrg6yhxfhkac.png)
which is the inverse of the function.
(b) Now if he charges $225 then we have,
![\begin{gathered} 225=75+49x \\ 49x=225-75 \\ 49x=150 \\ x=(150)/(49) \\ x=3.06 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jzjdtfomu7dzy5ab8bjenrpmwrynhvabc2.png)
so, the jobs last for 3.06 hours.